2000
DOI: 10.1016/s0092-8674(00)00038-6
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Control of Endocytosis in Dendritic Cells by Cdc42

Abstract: Dendritic cells (DCs) developmentally regulate antigen uptake by controlling their endocytic capacity. Immature DCs actively internalize antigen. However, mature DCs are poorly endocytic, functioning instead to present antigens to T cells. We have found that endocytic downregulation reflects a decrease in endocytic activity controlled by Rho family GTPases, especially Cdc42. Blocking Cdc42 function by Toxin B treatment or injection of dominant-negative inhibitors of Cdc42 abrogates endocytosis in immature DCs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
352
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 392 publications
(382 citation statements)
references
References 47 publications
29
352
0
1
Order By: Relevance
“…In the present work, we further characterize the earlier described capacity of iDC to internalize and process antigen for presentation on MHC class I [15][16][17]. We found that dispersed iDC can process exogenous OVA in an alternative, TAP-independent, BFA-and lactacystinresistant MHC class I pathway and that this function is rapidly lost as the cells mature in vitro.…”
Section: Introductionmentioning
confidence: 52%
“…In the present work, we further characterize the earlier described capacity of iDC to internalize and process antigen for presentation on MHC class I [15][16][17]. We found that dispersed iDC can process exogenous OVA in an alternative, TAP-independent, BFA-and lactacystinresistant MHC class I pathway and that this function is rapidly lost as the cells mature in vitro.…”
Section: Introductionmentioning
confidence: 52%
“…Thus, data obtained by use of exoenzyme C3 speak in favor of an important role of the DC's F-actin cytoskeleton without addressing the regulatory role(s) of individual GTPases. LPS exposure of immature bone marrow-derived murine DCs down-regulates active Cdc42 (13), while the same stimulus increases Cdc42 activity in murine splenic DCs (14). Rac1 (14) or Cdc42 (13) was found to be essential for the constitutive macropinocytosis of immature DCs.…”
Section: Endritic Cells (Dcs)mentioning
confidence: 96%
“…Rac1 (14) or Cdc42 (13) was found to be essential for the constitutive macropinocytosis of immature DCs. In the latter study, a down-regulated Cdc42 activity was functionally linked to the loss of macropinocytic activity in mature DCs (13). It is not decided whether the apparent discrepancy may relate to fundamental differences in Cdc42 regulation in different DC subtypes or may be due to variations in the detection levels of activated GTPases when they are bound to downstream targets in activated/mature DCs (15).…”
Section: Endritic Cells (Dcs)mentioning
confidence: 97%
See 1 more Smart Citation
“…In DCs exposed to Ag and maturational stimuli, such as LPS and TNF-␣, peptide loading is thought to occur in the MIIC, followed by transport of Ag-bound MHC class II molecules to the cell surface (4 -7). Concurrently, endocytosis is down-regulated, resulting in the accumulation of MHC class II/peptide complexes on the cell surface (8,9). These DC maturation-associated changes in MHC class II trafficking are critical for peptide Ag presentation.…”
Section: Endritic Cells (Dcs) 3 Capture Ags In Peripheral Tissuesmentioning
confidence: 99%